2019
DOI: 10.1021/acs.est.8b04523
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Important Contribution of Gas-Phase Oxidation of Naphthalene and Methylnaphthalene to Secondary Organic Aerosol during Haze Events in Beijing

Abstract: Naphthalene (Nap) and methylnaphthalene (MN) are the most abundant polycyclic aromatic hydrocarbons (PAHs) in atmosphere and have been proposed to be important precursors of anthropogenic secondary organic aerosol (SOA) derived from laboratory chamber experiments. In this study, atmospheric Nap/MN and their gas-phase photooxidation products were quantified by a Proton Transfer Reaction-Quadrupole interface Time-of-Flight Mass Spectrometer (PTR-QiTOF) during the 2016 winter in Beijing. Phthalic anhydride, a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 56 publications
(100 reference statements)
5
39
1
Order By: Relevance
“…In this study, we determine 2.8±4.6% of SOA in PRD and 11.1±14.3% of SOA in NCP are contributed by naphthalenes. The SOA contribution from naphthalenes determined for NCP is comparable to the results (10.2±1.0%) obtained during haze events in Beijing in a recent study (Huang et al, 2019). Significant contribution from monoterpenes to SOA (8.7±14.6%)…”
Section: Estimation Of the Contributions Of Higher Alkanes To Soa Forsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, we determine 2.8±4.6% of SOA in PRD and 11.1±14.3% of SOA in NCP are contributed by naphthalenes. The SOA contribution from naphthalenes determined for NCP is comparable to the results (10.2±1.0%) obtained during haze events in Beijing in a recent study (Huang et al, 2019). Significant contribution from monoterpenes to SOA (8.7±14.6%)…”
Section: Estimation Of the Contributions Of Higher Alkanes To Soa Forsupporting
confidence: 87%
“…PTR-MS using H3O + chemistry makes possible of quantitative of alkenes, aromatics, and even oxygenated VOCs (Yuan et al, 2017a). Here, PTR-MS with NO + chemistry was used to detect higher alkanes, through hydride abstraction by NO + forming mass (m-1) ions (m is the molecular mass) (Erickson et al, 2014;Koss et al, 2016;Inomata et al, 2013).…”
Section: No + Ptr-tof-ms Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, through mass spectrometric analysis of individual compounds, we find that for the Changchun− samples, formulas of C8H6O4, C7H6O2, C7H6O3, C8H8O2, and C8H8O3 with DBE values of 6, 5, 5, 5, and 5 dominate the assigned CHO formulas with respect to peak abundance. According to previous studies, C8H6O4, C7H6O2 and C7H6O3 are suggested to be phthalic acid, benzoic acid and monohydroxy benzoic acid, respectively, which are derived from naphthalene (Kautzman et al, 2010;Riva et al, 2015;Wang et al, 2017;He et al, 2018;Huang et al, 2019). C8H8O2 and C8H8O3 are likely 4-hydroxy acetophenone and 4-methoxybenzoic acid which could be derived from estragole (Lee et al, 2006;Pereira et al, 2014).…”
Section: Cho Compoundsmentioning
confidence: 95%
“…Detailed descriptions about the PTR-QiTOF measurements are provided elsewhere (Huang et al, 2019). The meteorological parameters including temperature, RH, barometric pressure, wind speed, and wind direction were acquired by a weather station at the same site (Met One Instruments Inc., 083E, 092, 010C, and 020C).…”
Section: Ambient Measurements and Data Processingmentioning
confidence: 99%